Persymmetric detectors with enhanced rejection capabilities. Issue 5 (1st June 2014) - Hao, Chengpeng; Orlando, Danilo; Ma, Xiaochuan; Yan, Shefeng; Hou, Chaohuan
Abstract : In this study, the authors deal with the problem of adaptive detection of point‐like targets in Gaussian disturbance with unknown but persymmetric structured covariance matrix induced by the space and/or time symmetry of the sensing system. In this framework, they devise and assess two selective receivers exploiting the Rao test and the generalised likelihood ratio test design criteria. The performance assessment, conducted by Monte Carlo simulation, has shown that the proposed receivers can significantly outperform their unstructured counterparts and guarantee enhanced rejection performance of unwanted signals with respect to their natural competitors.